PERANCANGAN PROTOTYPE APLIKASI MOBILE FRIZFOO MENGGUNAKAN METODE USER CENTERED DESIGN - limputra, Juan kristo; Sudirman; Thayf, Mohammad Sofyan S (STMIK KHARISMA Makassar, 2024)
This research involves the design of a mobile application prototype called Frizfoo using the User-Centered Design (UCD) approach to ensure the alignment between design and user needs. Primary data was obtained through interviews and observations of five Frizfoo users, using the